2011
DOI: 10.1103/physrevd.83.066005
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity in an anisotropic background

Abstract: By using the gauge/gravity duality, we investigate the dual field theories of the anisotropic backgrounds, which are exact solutions of Einstein-Maxwell-dilaton theory with a Liouville potential. When we turn on the bulk gauge field fluctuation A x with a nontrivial dilaton coupling, the AC conductivity of this dual field theory is proportional to the frequency with an exponent depending on parameters of the anisotropic background. In some parameter regions, we find that this conductivity can have the negative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…In this limit, the study of the transverse gauge fluctuation with nonzero frequency provides information about the AC conductivity, which reduces to the DC conductivity in the zero frequency limit [59]. In addition, we can find the shear viscosity from the bulk gravitational perturbation h xy .…”
Section: The Shear Viscosity and Ac Conductivity In The Zero Momentummentioning
confidence: 98%
“…In this limit, the study of the transverse gauge fluctuation with nonzero frequency provides information about the AC conductivity, which reduces to the DC conductivity in the zero frequency limit [59]. In addition, we can find the shear viscosity from the bulk gravitational perturbation h xy .…”
Section: The Shear Viscosity and Ac Conductivity In The Zero Momentummentioning
confidence: 98%
“…Recently, those works have been further generalized to the hyperscaling violation and Lifshitz geometries in which the asymptotic geometry is deviated from the AdS space and the boundary conformal symmetry is broken explicitly or spontaneously. [22][23][24][25][26][27][28][29][30][31][32][33] In these cases, the broken conformal symmetry can be realized by a nontrivial dilaton profile. It would be interesting to understand the nontrivial RG flow of the dual field theory from the corresponding classical gravity theory.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a nontrivial dilaton profile breaks the scaling symmetry without breaking the boundary Lorentz symmetry, so the dual theory represents a relativistic nonconformal field theory. [29][30][31][32][33] The other interesting example is the Lifshitz geometry which was invented to understand nonrelativistic features by using the holographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the gauge/gravity duality, the nontrivial dilaton profile can be identified with the running coupling constant of the dual gauge theory. It was also shown that the nontrivial dilaton coupling of the gauge fluctuation plays an important role to determine the properties of the dual gauge theory leading to the strange metallic behavior [20,21,23,30,54,55,56]. Therefore it is, indeed interesting to study hydrodynamic properties of the vector fluctuations with or without a nontrivial dialton profile.…”
Section: Properties Of the Non-conformal Dual Gauge Theorymentioning
confidence: 99%
“…which were also used for finding the generically hyperscaling violating solutions [20,21,23,24,26,27,28,29]. By rescaling the x and y coordinates, we can choose b 0 = 1 without any loss of generality.…”
Section: Einstein-dilaton Theorymentioning
confidence: 99%